MATHEMATICAL MODELLING OF THE ANALYTICAL AND NUMERICAL SOLUTION OF NON-STATIONARY INITIAL-VALUE PROBLEMS BY MAPLE SOFTWARE. - Sučkovs, Iļja; Pikurs, Aleksandrs; Kangro, Ilmārs (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2019)
With the passage of time and the development of technology, humanity is exploring new unknown problems that require complex analytical and numerical mathematical solutions. Due to their complexity differential equations are often used for this purpose. The aim of this work is to solve mathematical models of initial value problems of ordinary differential equations using the analitical method and numerical solution using MAPLE software. Also authors have provided general information about differential equations and diferent ways how they can be solved. As a result have been created two mathematical models which describe process of Determination of the cooling time of a shot animal and decomposition of the radioactive substance. Similar methods are also used to determine the age of objects as well